THE INFLUENCE OF COMMUNITY EMPOWERMENT THROUGH VILLAGE-OWNED ENTERPRISES (BUMDES) TO IMPROVE THE VILLAGE ECONOMY IN BARITO KUALA REGENCY - Ana Aulia; Monry Fraick Nicky Gillian Ratumbuysang; Mahmudah Hasanah; Maulana Rizky (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The purpose of this study was to determine the effect of community empowerment through BUMDes on improving the village economy in Barito Kuala Regency. The problem focused on the role of community empowerment through BUMDes to improve the economy of rural communities. Data was collected through observation, interview, questionnaire and documentation methods. Analyzed descriptively with a quantitative approach. The population used in this study were all administrators and parties involved in BUMDes. Sampling method using nonprobability sampling technique. The type of nonprobability sampling used is purposive sampling.Â The purposive sampling method obtained 54 samples. The analysis used is simple linear regression analysis, with the t test. The results showed that there was a positive influence between community empowerment through BUMDes on improving the village economy in Barito Kuala Regency. Based on hypothesis testing, it is known that the significance value (Sig.) of 0.036 is smaller than the probability of 0.05, so it can be concluded that there is a positive influence between community empowerment through BUMDes on Village Economic Improvement. The effect of community empowerment through BUMDes to improve the village economy in Barito Kuala Regency is 28.5%.